Application of Citizen Science to Sheep as a Model to Sensitize Young Citizens to Biodiversity, Animal Welfare and the Social Utility of Research - Sara Moscatelli; Anna Paniccià; Elisa Palmioli; Laura Del Gobbo; Francesca Mercati; Paola Scocco (Animals)
Citizen science activities were performed using sheep as an animal model and involving 252 students aged between 9 and 11 years. The study focused on three pillars: hill/mountain landscape biodiversity, animal welfare and the social utility of research. Two types of tests—“attitude questionnaires” (AQs) and “maximum performance tests” (MPTs)—were administered. The AQ was administered before and at the end of the project to compare the children’s sensitivity to the treated topics and to assess their awareness of the project’s pillars. For each AQ item children expressed their agreement/disagreement by choosing from five response modes. The MPT aim was to evaluate if children had understood the explained topics by true/false options in respect to a sentence. The correlations between MPT scores and school evaluations for science subjects were analyzed. Among the fifteen AQ items specific to the pillars, four items related to biodiversity, three items related to animal welfare and two items related to the social utility of research, showing a significant difference (p < 0.05) for the second AQ’s responses. Two items showed sex-related differences. The analysis of the data from the MPT showed that the didactic methodology used was effective and improved the position of most children by bringing them into higher science evaluation groups.